2019
DOI: 10.3166/phyto-2019-0217
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antifusarial Activity of a Tar Extracted from the Juniperus phoenicea L. Wild in Southwest of Algeria

Abstract: The biological activities of medicinal plants have been recognized for centuries. Among them, Juniperus phoenicea is very commonly used for its medicinal virtues (respiratory, hepatic and renal infections). Its wood is used for heating and manufacture of coal and its vegetable tar is used to treat certain cases of eczema. The aim of the present study is focused on the evaluation of the in vitro antifungal activity of a tar extracted from Juniperus phoenicea L. The physicochemical analysis was performed first; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Higher yields have been reported by different authors, 1.703%, 1.20%, 11.0% and 2.0%, respectively. 64,65,66,67 However, Loizzo et al reported 0.68% yield. 15 The yield of essential oil extraction from Cedrus atlantica wood was 4.03%, surpassing some previously reported results in the literature.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher yields have been reported by different authors, 1.703%, 1.20%, 11.0% and 2.0%, respectively. 64,65,66,67 However, Loizzo et al reported 0.68% yield. 15 The yield of essential oil extraction from Cedrus atlantica wood was 4.03%, surpassing some previously reported results in the literature.…”
Section: Resultsmentioning
confidence: 98%
“…67 J. oxycedrus EO derived from aerial parts contains compounds such as α-pinene and β-cedrene and phenols like guaiacol and cresol. 15,79 The tar of J. oxycedrus contains αpinene, γ-cadinene, and germacrene D. 65 Notably, the EO displays a higher concentration of alcohols compared to the oil distilled from empyreumatic (tar) oil. 78 Furthermore, the chemical compositions of J. oxycedrus essential oils vary across different regions, resulting in distinct majority compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Their lipophilic nature allows infiltrating and disrupting fungal cell membranes, causing leakage and ultimately celling death 100 , 101 . Sesquiterpenes (α-cedrene and β-caryophyllene) inhibit crucial fungal enzymes and metabolic pathways 102 . Phenolic compounds (thymol and carvacrol) are wielding their potent antioxidant properties to neutralize ROS generated by phytopathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The species' wide geographic distribution allows for a tremendous amount of genetic variability [17]. In folk medicine, this plant is considered a remedy that is commonly used in many countries for the treatment of diarrhea, bronchitis, rheumatism, acute gonococcal infection, eczema, hemorrhoids, dysmenorrheal, sunstroke, and depurative disinfectant [18,19]. The leaves of J. phoenicia are used against bronco-pulmonary disease and as a diuretic, whereas the berries are used to calm the crises of all types of coughs and as an oral hypoglycemic agent [20].…”
Section: Introductionmentioning
confidence: 99%